2023
DOI: 10.3389/fgene.2022.1054567
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two rare NPRL3 variants in two Chinese families with familial focal epilepsy with variable foci 3: NGS analysis with literature review

Abstract: Background: The GAP Activity Towards Rags 1 (GATOR1) complex, which includes DEPDC5, NPRL2, and NPRL3, plays a key role in epilepsy. It has been reported that focal epilepsy is associated with mutations in the NPRL3 gene in some cases. We report two rare mutations in the NPRL3 gene in two unrelated Chinese families with focal epilepsy in this study.Methods: The proband and her brother in family E1 first experienced seizures at 1.5 and 6 years of age, respectively. Despite resection of epileptogenic foci, she s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The clinical features of patients with different NPRL3 variants reported from published papers [ 6 , 9 , 10 ] and our study have been listed in Table 3 to deepen our understanding of the newly discovered gene variant. Most patients had adolescent-onset disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical features of patients with different NPRL3 variants reported from published papers [ 6 , 9 , 10 ] and our study have been listed in Table 3 to deepen our understanding of the newly discovered gene variant. Most patients had adolescent-onset disease.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI findings varied; they could be normal or abnormal. The genetic testing findings are as follows: Weckhuysen et al 2016 [ 6 ] found five patients had NPRL3 : c.1270C>T, p.Arg424* and four patients had NPRL3 : c.1070delC, p.Pro357Hisfs*56; Li et al 2021 [ 9 ] found five patients had NPRL3 : c316C>T, p. Q106*; Hu et al 2022 [ 10 ] found two patients had NPRL3 : c.954C>A, p.Y318* and one patient had NPRL3 : c.1545-1G>C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations